The geology of the western Nuba Mountains region South Kordofan State Sudan with special emphasis on the low-grade Neoproterozoic meta-volcano-sedimentary sequence - Bumby, Adam John (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.